2017
DOI: 10.1155/2017/6468097
|View full text |Cite
|
Sign up to set email alerts
|

Sustained High Levels of Both Total and High Molecular Weight Adiponectin in Plasma during the Convalescent Phase of Haemorrhagic Fever with Renal Syndrome Are Associated with Disease Severity

Abstract: Haemorrhagic fever with renal syndrome (HFRS) is characterised by an uncontrolled immune response that causes vascular leakage. Adiponectin (APN) is an adipocytokine involved in prorevascularisation and immunomodulation. To investigate the possible effects of APN in the pathogenesis of HFRS, total and high molecular weight (HMW) APN levels in the plasma of patients with HFRS were quantified using enzyme-linked immunosorbent assay (ELISA). Compared with those in healthy controls, the plasma total and HMW APN le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…At the acute phase of HFRS patients, levels of TNF-α and IL-1β in serum were significantly elevated [5], which may increase the secretion of IL-34 from above immune cells and tissue cells and contribute to the elevation of plasma IL-34 levels. In our previous study, we found that level of plasma adiponectin, which is predominantly secreted by adipocytes, was significantly elevated in HFRS, suggesting that systemic inflammatory response influenced the function of adipocytes in patients with HFRS [33]. The systemic inflammatory response during HTNV infection may also promote the secretion of IL-34 by adipocytes.…”
Section: Discussionmentioning
confidence: 90%
“…At the acute phase of HFRS patients, levels of TNF-α and IL-1β in serum were significantly elevated [5], which may increase the secretion of IL-34 from above immune cells and tissue cells and contribute to the elevation of plasma IL-34 levels. In our previous study, we found that level of plasma adiponectin, which is predominantly secreted by adipocytes, was significantly elevated in HFRS, suggesting that systemic inflammatory response influenced the function of adipocytes in patients with HFRS [33]. The systemic inflammatory response during HTNV infection may also promote the secretion of IL-34 by adipocytes.…”
Section: Discussionmentioning
confidence: 90%
“…9 Many new biomarkers such as high molecular weight Adiponectin (HMW APN), soluble CD138, platelet distribution width (PDW) and high mobility group box protein-1 (HMGB-1) have been reported to be associated with the severity of orthohantavirus infection. [11][12][13][14] However, there is still a lack of effective markers for early diagnosis and monitoring of disease progression for HFRS.…”
Section: Introductionmentioning
confidence: 99%